Fe-doped ZIF-67 derivative catalyst, preparation method and application of Fe-doped ZIF-67 derivative catalyst in electro-catalytic oxygen evolution

Through the preparation of Fe-doped ZIF-67 derivative catalyst, the high barrier and low kinetic velocity of the oxygen evolution reaction during the electrolytic hydrogen production process was solved, and efficient electrocatalytic oxygen evolution performance and low waste liquid pollution were achieved.

CN119824453APending Publication Date: 2025-04-15XIAN THERMAL POWER RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510041979.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The oxygen evolution reaction (OER) involved in the prior art during the electrolytic hydrogen production process has high reaction barriers and low kinetic velocity, resulting in high overpotential and high energy consumption, limiting the widespread application of electrolytic water technology.

Method used

Fe-doped ZIF-67 derivative catalyst is used to insulate Fe2O3@CNHs/ZIF-67 powder and S powder under argon for 20-30 minutes to form Fe-doped ZIF-67 derivative catalyst, which avoids the use of solvents and reduces waste liquid contamination.

Benefits of technology

The nanocomposite oxygen evolution performance is achieved. The nanocomposite oxygen evolution electrocatalyst can drive the current density of 10mA cm-2 and 100mA cm-2 in 1 mol/L KOH solution, which significantly improves the reaction rate and stability of OER catalyzed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and discloses a Fe-doped ZIF-67 derivative catalyst, a preparation method and application of the Fe-doped ZIF-67 derivative catalyst to electro-catalytic oxygen evolution, and the preparation method comprises the following steps: in argon, carrying out heat preservation on Fe2O3 (at) CNHs / ZIF-67 powder and S powder at 500-550 DEG C for 20-30 minutes; according to the method for introducing heterogeneous metal doping, additional chemical reagents and absolute ethyl alcohol do not need to be added into the formed ZIF-67 for repeated cleaning, and the problem of environmental pollution caused by a solvent is avoided. Fe2O3 (at) CNHs / ZIF-67 powder and S powder are subjected to heat preservation at a high temperature, in the sulfuration process, an organic framework ZIF-67 is pyrolyzed at the high temperature, Fe2O3 is reduced, Fe is doped into CoS2 crystals, and the Fe-doped ZIF-67 derivative catalyst is formed. After high-temperature vulcanization, the CNHs have a certain supporting effect on a collapsed carbon skeleton of the ZIF-67, and the stability of electro-catalysis oxygen evolution is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to an Fe-doped ZIF-67 derivative catalyst, a preparation method and application of the catalyst in electrocatalytic oxygen evolution. Background Art

[0002] As the most promising clean energy in the 21st century, hydrogen energy has great application potential in other industries such as electricity, aerospace, metallurgy, etc. It is one of the important methods to solve the problems of global warming and environmental pollution. Hydrogen production by water electrolysis is an efficient and environmentally friendly method of hydrogen production. However, the oxygen evolution reaction (OER) involved in the process of water electrolysis is a complex four-electron transfer process with high reaction barriers and slow kinetics. These characteristics lead to high overpotential and high energy consumption in the catalytic reaction, which hinders the widespread application of water electrolysis technology. Efficient electrocatalysts are crucial to increase the reaction rate of OER and minimize energy input by reducing overpotential. At present, precious metal catalysts are widely regarded as the most efficient and stable OER catalysts. However, precious metal catalysts cannot meet the needs of practical applications due to their high price, rare production and limited durability. Therefore, creating efficient and reasonably priced OER catalysts is one of the major challenges in promoting the development of water electrolysis technology.

[0003] Metal-Organic Frameworks (MOF) are a special type of coordination polymer, consisting of organic ligands (especially O and N) and a series of transition metal ions. MOF has unique chemical and physical properties, including a regular pore structure, abundant metal ions, unsaturated active sites, a high specific surface area, and an easily modified surface. Therefore, it is an ideal choice for catalysts. Studies have shown that ZIF-67 (a Co-based MOF), as a type of MOF, Co ions will be reduced at high temperatures under inert gas, and the organic ligands of ZIF-67 will be carbonized at high temperatures to form a N-doped carbon skeleton. If the inert gas is changed to sulfur vapor, the Co atoms will generate cobalt sulfur compounds, further improving the electrocatalytic oxygen evolution performance.

[0004] Further studies have shown that introducing heterogeneous metal atoms into transition metal compounds on MOFs is an effective strategy to improve electrochemical performance. Metal element doping can adjust the electronic structure, increase active sites, form a synergistic effect, improve conductivity and stability, and effectively promote the kinetics of electrocatalytic reactions. However, the current method of introducing heterogeneous metal elements is mainly through the addition of heterogeneous metal ion reagents (Fe-Doped CoS2Nanocages as BifunctionalElectrocatalysts for Water Splitting, Bo Fang, Yue Li, Jiaqi Yang, Ting Lu, Xinjuan Liu, Xiaohong Chen, Likun Pan, and Zhenjie Zhao, ACS Appl. Nano Mater. 2024, 7, 9685−9695), and then repeatedly washing with anhydrous ethanol and deionized water. This method will cause a large amount of waste liquid pollution. Summary of the invention

[0005] In order to overcome the technical problem of waste liquid pollution in the prior art, the purpose of the present invention is to provide an Fe-doped ZIF-67 derivative catalyst and a preparation method and its application in electrocatalytic oxygen evolution. The Fe-doped ZIF-67 derivative catalyst prepared by this method does not use a solvent, thereby avoiding the problem of waste liquid polluting the environment.

[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a Fe-doped ZIF-67 derivative catalyst comprises the following steps: Under argon, Fe2O3@CNHs / ZIF-67 powder and S powder were kept at 500-550℃ for 20-30 minutes to obtain Fe-doped ZIF-67 derivative catalyst.

[0007] A further improvement of the present invention is that the mass ratio of Fe2O3@CNHs / ZIF-67 powder to S powder is 1:3-1:5. A further improvement of the present invention is that the Fe2O3@CNHs / ZIF-67 powder is prepared by the following process: 1) Add Co(NO3)2·6H2O or CoCl2·6H2O to a solution containing Fe2O3@CNHs powder, dimethylformamide and polyvinylpyrrolidone and stir to form a deposited Co 2+ Fe2O3@CNHs; 2) Deposition of Co 2+2-Methylimidazole, Co(NO3)2·6H2O and dimethylformamide were added to Fe2O3@CNHs and reacted by solvothermal method to obtain a nanocomposite catalyst.

[0008] A further improvement of the present invention is that in step 1), the dosage ratio of Fe2O3@CNHs powder, dimethylformamide, polyvinyl pyrrolidone and Co(NO3)2·6H2O or the dosage ratio of Fe2O3@CNHs powder, dimethylformamide, polyvinyl pyrrolidone and CoCl2·6H2O is 30-35 mg: 30-35 ml: 0.30-0.40 g: 2.91 -3.00 g.

[0009] A further improvement of the present invention is that in step 2), the usage ratio of 2-methylimidazole, Co(NO3)2·6H2O and dimethylformamide is 0.66-0.70 g: 0.58-0.60 g: 40-50 ml, and the usage ratio of 2-methylimidazole, CoCl2·6H2O and dimethylformamide is 0.66-0.70 g: 0.58-0.60 g: 40-50 ml.

[0010] A further improvement of the present invention is that the reaction temperature is 130-140° C. and the reaction time is 24-26 hours.

[0011] A further improvement of the present invention is that the Fe2O3@CNHs powder is prepared by a positive pressure arc discharge method.

[0012] A further improvement of the present invention is that the Fe2O3@CNHs powder is prepared by the following process: a graphite rod is used as a cathode and an anode, a Fe wire is inserted into the anode graphite rod, and discharge is performed under a mixed gas of nitrogen and argon, the voltage between the cathode and the anode is 30 V, and the discharge current is 100-150 A to obtain a product, and the product is heated at 400-550°C for 30-60min to obtain Fe2O3@CNHs powder.

[0013] An Fe-doped ZIF-67 derivative catalyst prepared according to the method of claims 1-8.

[0014] A method for preparing a Fe-doped ZIF-67 derivative catalyst prepared according to the method of claims 1-8 and its application in an electrocatalytic oxygen evolution reaction.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The method of introducing heterogeneous metal doping in the present invention does not require the addition of additional chemical reagents and repeated washing with anhydrous ethanol to the formed ZIF-67, thereby avoiding the problem of environmental pollution caused by solvents. The Fe source carrier Fe2O3@CNHs (CNHs is carbon nanohorn) also has a certain electrocatalytic oxygen evolution activity, providing active sites, so that the final Fe-doped ZIF-67 derivative catalyst has a higher electrocatalytic oxygen evolution activity. In the present invention, Fe2O3@CNHs / ZIF-67 powder and S powder are kept at 500-550°C for 20-30 minutes to obtain a Fe-doped ZIF-67 derivative catalyst. During the sulfurization process, the organic framework ZIF-67 is pyrolyzed at high temperature, resulting in the reduction of Fe2O3, and Fe is doped into the CoS2 crystal to form a Fe-doped ZIF-67 derivative catalyst. After high-temperature sulfurization, CNHs has a certain supporting effect on the collapsed carbon skeleton of ZIF-67, maintaining the stability of electrocatalytic oxygen evolution. Nanocomposite oxygen evolution electrocatalyst driven at 10 mA cm in 1 mol / L KOH solution -2 and 100 mAcm -2 Only 183 mV and 340 mV overpotentials are required at current densities of 1.3–2.5 GHz, respectively, showing extremely high potential in OER catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the preparation of Fe2O3@CNHs; Figure 2 This is the process flow chart for the preparation of Fe2O3@CNHs / Fe-CoS2@NC; Figure 3 Figures 2 and 3 show the structural determination diagrams of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs; (a) is the scanning electron microscope image of Fe2O3@CNHs / ZIF-67; (b) is the element spectrum of Fe2O3@CNHs / ZIF-67; (cd) are the TEM images of Fe2O3@CNHs / ZIF-67; (ef) are the HRTEM images; (g) is the scanning electron microscope image of Fe2O3@CNHs; and (h) is the HRTEM image of Fe2O3@CNHs.

[0017] Figure 4 (a) Structural determination diagrams of Fe2O3@CNHs / Fe-CoS2@NC and CoS2; (b) SEM images of Fe2O3@CNHs / Fe-CoS2@NC; (cg) elemental spectrum of Fe2O3@CNHs / Fe-CoS2@NC; (hk) TEM image of Fe2O3@CNHs / Fe-CoS2@NC; HRTEM image of CoS2.

[0018] Figure 5 These are contact angle test diagrams, where (a) is the product (CoS2@NC) formed after high-temperature sulfurization of ZIF-67 without providing Fe source; (b) is the contact angle test of Fe2O3@CNHs / Fe-CoS2@NC.

[0019] Figure 6 XRD results, among which (a) is the XRD results of ZIF-67 and Fe2O3@CNHs / ZIF-67, and (b) is the XRD results of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC.

[0020] Figure 7 is the XPS graph of Fe2O3@CNHs / Fe-CoS2@NC; (a) is the XPS graph; (bf) are the high-resolution spectra of the elements; Figure 8 Performance diagrams of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC, where (a) is the LSV curve; (b) is the Tafel slope; (c) is the ECSA diagram; (d) is the EIS impedance diagram; (e) is the LSV curve and chronopotentiometry stability curve before and after 15 hours of testing. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0022] The design idea of ​​the preparation method of the Fe-doped ZIF-67 derivative of the present invention is to introduce heterogeneous metal atoms into the MOF base without using a large amount of chemical reagents, and to encapsulate the nanoparticles Fe2O3 in the carbon nanohorns (Fe2O3@CNHs) by a simple positive pressure arc discharge method and oxidation process. Then, Fe2O3@CNHs is loaded on ZIF-67 by a solvothermal method to obtain a nanocomposite catalyst (Fe2O3@CNHs / ZIF-67). Subsequently, during the sulfurization process, the organic framework ZIF-67 is pyrolyzed at high temperature, resulting in the reduction of Fe2O3, and Fe is doped into the CoS2 crystal to form the Fe-doped ZIF-67 derivative Fe2O3@CNHs / Fe-CoS2@NC. This nanocomposite oxygen evolution electrocatalyst drives 10mA cm in 1 mol / L KOH solution. -2 and 100 mA cm -2Only 183 mV and 340 mV overpotentials are required at current densities of 1.3–2.5 GHz, respectively, showing extremely high potential in OER catalysis.

[0023] The present invention provides a method for preparing a Fe-doped ZIF-67 derivative catalyst, comprising the following steps: (1) Preparation of Fe2O3@CNHs: Figure 1 The positive pressure arc discharge method shown in the figure uses high purity graphite rods (99.9%) as cathode and anode, wherein a graphite rod with a diameter of 15 mm and a length of 150 mm is used as cathode, a graphite rod with a diameter of 6 mm and a length of 200 mm is used as anode, and a Fe wire with a length of 50 mm and a diameter of 0.3 mm is inserted into the anode graphite rod. After the electric arc furnace is evacuated, nitrogen gas with a pressure of 0.01-0.05 MPa and argon gas with a pressure of 0.11-0.15 MPa are introduced. During the discharge process, the voltage between the cathode and the anode is 30 V, and the discharge current is 100-150 A. Finally, the products deposited on the inner cavity wall are collected. Then the generated product is placed in a tubular furnace, heated to 400-550℃, and kept warm for 30-60min, and finally Fe2O3 particles (i.e., Fe2O3@CNHs) coated with carbon nanohorns are formed.

[0024] (2) Synthesis of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC: 30-35 mg of Fe2O3@CNHs powder was immersed in a mixed solution of 30-35 ml of dimethylformamide (DMF) and 0.30-0.40 g of polyvinylpyrrolidone (PVP) to obtain a mixture.

[0025] Then, 2.91-3.00 g Co(NO3)2·6H2O or CoCl2·6H2O was added to the mixture and stirred for 12-15 hours to form a deposited Co 2+ Fe2O3@CNHs. Subsequently, a 40-50 ml DMF mixed solution containing 0.66-0.70 g 2-Methylimidazole and 0.58-0.60 g Co(NO3)2·6H2O was added and reacted by solvothermal method at 130-140°C for 24-26 hours. After washing and centrifugation, the nanocomposite catalyst Fe2O3@CNHs / ZIF-67 powder was obtained, as shown in the schematic diagram. Figure 2 shown.

[0026] Then, Fe2O3@CNHs / ZIF-67 powder and S powder were placed in a tube furnace, argon gas with a purity of 99.99% was introduced, and the mixture was heated to 500-550°C and kept warm for 20-30 minutes to obtain Fe-doped ZIF-67 derivatives called nanocomposite oxygen evolution electrocatalysts Fe2O3@CNHs / Fe-CoS2@NC. The mass ratio of Fe2O3@CNHs / ZIF-67 powder to S powder was 1:3-1:5. The preparation process is as follows Figure 2 shown.

[0027] Example 1 A method for preparing a Fe-doped ZIF-67 derivative comprises the following steps: (1) Preparation of Fe2O3@CNHs: Figure 1 The positive pressure arc discharge method shown in the figure uses high-purity graphite rods (99.9%) as cathodes and anodes, wherein a graphite rod with a diameter of 15 mm and a length of 150 mm is used as the cathode, a graphite rod with a diameter of 6 mm and a length of 200 mm is used as the anode, and a Fe wire with a length of 50 mm and a diameter of 0.3 mm is inserted into the anode graphite rod. After the arc furnace is evacuated, nitrogen gas with a pressure of 0.02 MPa and argon gas with a pressure of 0.13 MPa are introduced. During the discharge process, the voltage between the cathode and the anode is 30 V, and the discharge current is 110 A. Finally, the products deposited on the inner cavity wall are collected. The generated product is then placed in a tubular furnace, heated to 450 °C, and kept warm for 30 minutes, and finally Fe2O3 particles coated with carbon nanohorns (i.e., Fe2O3@CNHs) are formed.

[0028] (2) Synthesis of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC: 30 mg of Fe2O3@CNHs powder was immersed in a mixed solution of 30 ml of dimethylformamide (DMF) and 0.30 g of polyvinylpyrrolidone (PVP) to obtain a mixture. Then, 2.91 g of Co(NO3)2·6H2O was added to the mixture and stirred for 12 h to form a deposited Co 2+ Fe2O3@CNHs. Subsequently, a 40 ml DMF mixed solution containing 0.66 g 2-Methylimidazole and 0.58 g Co(NO3)2·6H2O was added and reacted by solvothermal method at 130°C for 24 hours. After washing and centrifugation, the nanocomposite catalyst Fe2O3@CNHs / ZIF-67 powder was obtained, as shown in the schematic diagram. Figure 2 shown.

[0029] Then, Fe2O3@CNHs / ZIF-67 powder and S powder were placed in a tube furnace, argon gas with a purity of 99.99% was introduced, heated to 500°C, and kept warm for 20 minutes. The resulting material was called Fe2O3@CNHs / Fe-CoS2@NC. The mass ratio of Fe2O3@CNHs / ZIF-67 powder to S powder was 1:3-1:5. The preparation process is as follows Figure 2 shown.

[0030] (3) Morphological characterization Figure 3 (g) is the TEM image of Fe2O3@CNHs, and it is observed that the size and dispersion of the metal particles encapsulated in CNHs have changed significantly. Figure 3 The HRTEM image in (h) shows that the lattice spacing of the metal nanoparticles is 0.271 nm, corresponding to the (222) crystal plane of Fe2O3, demonstrating the successful preparation of Fe2O3@CNHs. Figure 3 The scanning electron microscope images in (a)-(b) show that the metal nanoparticles are attached to the dodecahedron material, which is the morphological feature of ZIF-67. The elemental spectrum obtained using EDS shows the simultaneous presence of C, N, O, Fe, and Co elements, providing evidence for the successful synthesis of ZIF-67. In addition, Figure 3 The TEM images in (c)-(f) clearly show the metal particles attached to ZIF-67. Figure 3 The HRTEM images in (ef) show obvious lattice fringes with a lattice spacing of 0.271 nm, corresponding to the (222) plane of Fe2O3. This result confirms the successful preparation of Fe2O3@CNHs / ZIF-67.

[0031] The scanning electron microscope images in (a)-(b) in Figure 4 show that after high-temperature sulfurization, Fe2O3@CNHs / ZIF-67 presents flower-like distributed lamellar carbon on the outside. In addition, metal nanoparticles are uniformly dispersed in the lamellar carbon material. Figure 4 In (c)-(g), elemental analysis using EDS shows the simultaneous presence of C, N, O, Co and S elements. Figure 4 The TEM images in (h)-(j) show that ZIF-67 is transformed into many thick carbon material layers after high-temperature calcination. In addition, black metal particles can be seen dispersed in it. Figure 4In (k), the interplanar spacing can be measured by HRTEM images and determined to be 0.276 nm, corresponding to the (200) plane of CoS2. This finding confirms the successful synthesis of Fe2O3@CNHs / Fe-CoS2@NC. It is worth noting that no iron-based compounds were observed in both the TEM images and HRTEM measurements of CoS2. This indicates that during the high-temperature sulfurization process, the reducing gases produced by the pyrolysis of the organic framework of ZIF-67 reduced Fe2O3, resulting in Fe doping into the CoS2 lattice without the formation of a new phase.

[0032] See the products formed Figure 5 In (a) and (b), it can be seen that the contact angle of the product (CoS2@NC) formed by high-temperature sulfurization of ZIF-67 without Fe source is significantly smaller than that of the product (Fe2O3@CNHs / Fe-CoS2@NC) formed by high-temperature sulfurization of ZIF-67 with Fe source, further proving that Fe is incorporated into the CoS2 lattice.

[0033] (4) Phase characterization: Figure 6 (a) shows the XRD pattern of the sample. The characteristic diffraction peaks of Fe2O3@CNHs / ZIF-67 synthesized in this study are very close to the characteristic diffraction peaks of ZIF-67 reported in the literature. The presence of characteristic diffraction peaks corresponding to Fe2O3 in Fe2O3@CNHs / ZIF-67 confirms the successful preparation of the composite material. Compared with the standard peaks of ZIF-67, the position of the characteristic diffraction peaks of Fe2O3@CNHs / ZIF-67 does not shift significantly. This proves that after combining ZIF-67 and Fe2O3@CNHs, the catalyst framework does not undergo lattice distortion or significant expansion. Therefore, the addition of Fe2O3@CNHs does not affect the successful synthesis of ZIF-67. like Figure 6As shown in (b), the XRD characteristic diffraction peaks of Fe2O3@CNHs / Fe-CoS2@NC do not show peaks corresponding to ZIF-67. This indicates that the ZIF-67 organic framework decomposes at high temperatures. The characteristic diffraction peaks observed in Fe2O3@CNHs / Fe-CoS2@NC are mainly attributed to CoS2. These peaks are located at 32.3°, 36.2°, 46.3° and 54.9°, corresponding to the (200), (210), (211) and (311) crystal planes of CoS2, which is consistent with the results of lattice spacing in HRTEM. Compared with the standard CoS2 characteristic peaks, the characteristic peaks of Fe2O3@CNHs / Fe-CoS2@NC are slightly shifted toward the high binding energy direction, indicating that smaller Fe nanoparticles are incorporated into CoS2. The XRD patterns of Fe2O3@CNHs / Fe-CoS2@NC do not show any diffraction peaks associated with iron-based compounds, indicating that all metal nanoparticles were completely sulfurized into metal sulfides during the sulfurization process, proving the successful incorporation of iron atoms into CoS2.

[0034] See also Figure 7 In (a)-(f), XPS results show that the surface of Fe2O3@CNHs / Fe-CoS2@NC is mainly composed of Co, Fe, O, N, C and S, such as Figure 7 As shown in (a). Figure 7 In (b), the high-resolution N1s spectrum shows three characteristic peaks at 399.3 eV, 400.4 eV and 401.9 eV, which belong to pyridinic-N, pyrrolic-N and graphitic-N, respectively. Among them, pyridinic-N and graphitic-N have been identified as effective active sites for OER. In addition, the characteristic peaks of Co 2p can be divided into Co 2p 3 / 2 and Co 2p 1 / 2 , 779.7 eV and 795.4 eV respectively ( Figure 7 (d)). Strong characteristic peaks corresponding to Co-O bonds also appeared at 782.6 eV and 799.1 eV. This may be due to the oxidation of CoS2 after long-term exposure to air. The peaks observed at 786.1 eV and 804.6 eV are satellite peaks of CoS2. Figure 7 In (e), two characteristic peaks at 716.0 eV and 720.0 eV appear, which are known to appear in Fe-doped Co-based compounds. In addition, the two characteristic peaks at 724.0 eV and 710.2 eV correspond to Fe 2+ 2p 1 / 2 and Fe 2+ 2p 3 / 2 The other two characteristic peaks at 726.0 eV and 713.4 eV are respectively related to Fe3 + 2p 3 / 2 and Fe 3+ 2p 3 / 2 Figure 7 (f) shows the S 2p Spectrum, where the peak at 163.0 eV represents the metal (Co, Fe)-S bond. The peaks at 168.8 eV and 170.0 eV belong to SO4 2- .

[0035] (5) Performance test: The OER performance of the samples was tested using a three-electrode system in an alkaline electrolyte (1 mol / L KOH solution). All samples showed excellent catalytic performance, especially Fe2O3@CNHs / Fe-CoS2@NC. Figure 8 As shown in (a), Fe2O3@CNHs / Fe-CoS2@NC can drive 10 mA cm at an overpotential of only 183 mV. -2 The current density is 340 mV, which can drive 100 mA cm -2 . This result can be attributed to the unique nanostructure of Fe-CoS2 and the provision of effective active sites; the lamellar carbon material formed by the pyrolysis of the ZIF-67 organic framework forms a conductive network with CNHs, which promotes effective electron transfer during the catalytic process. The Tafel slope is one of the key parameters for evaluating OER catalytic performance. The lower the Tafel slope, the better the OER catalytic performance. Figure 8 As shown in (b), the Tafel slope values ​​of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC are 64.06 mV dec, respectively. -1 and 56.35 mV dec -1 This result shows that Fe2O3@CNHs / Fe-CoS2@NC has a more significant OER kinetic process. Figure 8 As shown in (c), the Cdl of Fe2O3@CNHs / ZIF-67 is 35.4 mF cm -2 , which is larger than the Cdl of Fe2O3@CNHs / Fe-CoS2@CNHs (6.0 mF cm -2), which indicates that Fe2O3@CNHs / ZIF-67 can provide a larger catalytic surface area and expose more active sites. This is because after high-temperature sulfurization, the ZIF-67 organic framework is carbonized, thereby reducing the catalytic area. However, despite the smaller ECSA, Fe2O3@CNHs / Fe-CoS2@CNHs still exhibits better catalytic performance, which is because Fe-CoS2 nanoparticles have more outstanding intrinsic catalytic activity. Figure 8 The EIS results in (d) show that the Rct value of Fe-CoS2@CNHs / NC is the lowest. This is because the synergistic effect of the lamellar carbon material formed by the high-temperature decomposition of ZIF-67 in Fe-CoS2@CNHs / NC and the carbon nanohorns effectively improves the conductivity and electron transfer efficiency of the catalyst, thereby reducing the charge transfer resistance value and promoting the reaction between the electrode interface and the electrolyte. The stability test was carried out by chronopotentiometry, such as Figure 8 As shown in (e). After 15 h of stability test, the catalytic performance of Fe2O3@CNHs / Fe-CoS2@NC did not decrease significantly, indicating that it has good catalytic stability. It is proved that the lamellar carbon material formed by high-temperature decomposition and carbonization of ZIF-67 improves the dispersibility of Fe-CoS2 due to its unique structure, inhibits the agglomeration of Fe-CoS2 during the catalytic process, and improves the stability of the composite catalyst in the OER process.

[0036] Example 2 A method for preparing a Fe-doped ZIF-67 derivative comprises the following steps: (1) Preparation of Fe2O3@CNHs: Figure 1 The positive pressure arc discharge method shown in the figure uses high-purity graphite rods (99.9%) as cathodes and anodes, wherein a graphite rod with a diameter of 15 mm and a length of 150 mm is used as the cathode, and a graphite rod with a diameter of 6 mm and a length of 200 mm is used as the anode, and a Fe wire with a length of 50 mm and a diameter of 0.3 mm is inserted into the anode graphite rod. After the arc furnace is evacuated, nitrogen gas with a pressure of 0.01 MPa and argon gas with a pressure of 0.11 MPa are introduced. During the discharge process, the voltage between the cathode and the anode is 30 V, and the discharge current is 130 A. Finally, the products deposited on the inner cavity wall are collected. Then the generated product is placed in a tubular furnace, heated to 400 °C, and kept warm for 60 minutes, and finally Fe2O3 particles coated with carbon nanohorns (i.e., Fe2O3@CNHs) are formed.

[0037] (2) Synthesis of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC: 33 mg of Fe2O3@CNHs powder was immersed in a mixed solution of 35 ml of dimethylformamide (DMF) and 0.40 g of polyvinylpyrrolidone (PVP) to obtain a mixture. Then, 2.91 g of Co(NO3)2·6H2O was added to the mixture and stirred for 12 h to form a deposited Co 2+ Fe2O3@CNHs. Subsequently, a 50 ml DMF mixed solution containing 0.70 g 2-Methylimidazole and 0.58 g Co(NO3)2·6H2O was added and reacted at 130°C by solvothermal method for 26 hours. After washing and centrifugation, the nanocomposite catalyst Fe2O3@CNHs / ZIF-67 powder was obtained.

[0038] Subsequently, the Fe2O3@CNHs / ZIF-67 powder and S powder were placed in a tube furnace, and argon gas with a purity of 99.99% was introduced, heated to 500°C, and kept warm for 30 minutes. The resulting material was called Fe2O3@CNHs / Fe-CoS2@NC. The mass ratio of Fe2O3@CNHs / ZIF-67 powder to S powder was 1:4.

[0039] Example 3 A method for preparing a Fe-doped ZIF-67 derivative comprises the following steps: (1) Preparation of Fe2O3@CNHs: Figure 1 The positive pressure arc discharge method shown in the figure uses high-purity graphite rods (99.9%) as cathodes and anodes, wherein a graphite rod with a diameter of 15 mm and a length of 150 mm is used as the cathode, and a graphite rod with a diameter of 6 mm and a length of 200 mm is used as the anode, and a Fe wire with a length of 50 mm and a diameter of 0.3 mm is inserted into the anode graphite rod. After the arc furnace is evacuated, nitrogen gas with a pressure of 0.03 MPa and argon gas with a pressure of 0.15 MPa are introduced. During the discharge process, the voltage between the cathode and the anode is 30 V, and the discharge current is 150 A. Finally, the products deposited on the inner cavity wall are collected. Then the generated product is placed in a tubular furnace, heated to 550 °C, and kept warm for 30 minutes, and finally Fe2O3 particles coated with carbon nanohorns (i.e., Fe2O3@CNHs) are formed.

[0040] (2) Synthesis of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC: 35 mg of Fe2O3@CNHs powder was immersed in a mixed solution of 32 ml of dimethylformamide (DMF) and 0.35 g of polyvinylpyrrolidone (PVP) to obtain a mixture. Then, 3.00 g of Co(NO3)2·6H2O was added to the mixture and stirred for 15 h to form a deposited Co 2+ Fe2O3@CNHs. Subsequently, a 45 ml DMF mixed solution containing 0.68 g 2-Methylimidazole and 0.60 g Co(NO3)2·6H2O was added and reacted at 135°C by solvothermal method for 25 hours. After washing and centrifugation, the nanocomposite catalyst Fe2O3@CNHs / ZIF-67 powder was obtained.

[0041] Subsequently, the Fe2O3@CNHs / ZIF-67 powder and S powder were placed in a tube furnace, and argon gas with a purity of 99.99% was introduced, heated to 520°C, and kept warm for 25 minutes. The resulting material was called Fe2O3@CNHs / Fe-CoS2@NC. The mass ratio of Fe2O3@CNHs / ZIF-67 powder to S powder was 1:5.

[0042] Example 4 A method for preparing a Fe-doped ZIF-67 derivative comprises the following steps: (1) Preparation of Fe2O3@CNHs: Figure 1 The positive pressure arc discharge method shown in the figure uses high-purity graphite rods (99.9%) as cathodes and anodes, wherein a graphite rod with a diameter of 15 mm and a length of 150 mm is used as the cathode, and a graphite rod with a diameter of 6 mm and a length of 200 mm is used as the anode, and a Fe wire with a length of 50 mm and a diameter of 0.3 mm is inserted into the anode graphite rod. After the arc furnace is evacuated, nitrogen gas with a pressure of 0.05 MPa and argon gas with a pressure of 0.15 MPa are introduced. During the discharge process, the voltage between the cathode and the anode is 30 V, and the discharge current is 100 A. Finally, the products deposited on the inner cavity wall are collected. Then the generated product is placed in a tubular furnace, heated to 500 °C, and kept warm for 40 minutes, and finally Fe2O3 particles coated with carbon nanohorns (i.e., Fe2O3@CNHs) are formed.

[0043] (2) Synthesis of Fe2O3@CNHs / ZIF-67 and Fe2O3@CNHs / Fe-CoS2@NC: 30 mg of Fe2O3@CNHs powder was immersed in a mixed solution of 30 ml of dimethylformamide (DMF) and 0.30 g of polyvinylpyrrolidone (PVP) to obtain a mixture. Then, 2.95 g of Co(NO3)2·6H2O was added to the mixture and stirred for 14 h to form a deposited Co 2+ Fe2O3@CNHs. Subsequently, a 42 ml DMF mixed solution containing 0.70 g 2-Methylimidazole and 0.59 g Co(NO3)2·6H2O was added and reacted at 140°C by solvothermal method for 24 hours. After washing and centrifugation, the nanocomposite catalyst Fe2O3@CNHs / ZIF-67 powder was obtained.

[0044] Subsequently, the Fe2O3@CNHs / ZIF-67 powder and S powder were placed in a tube furnace, and argon gas with a purity of 99.99% was introduced, heated to 550°C, and kept warm for 20 minutes. The resulting material was called Fe2O3@CNHs / Fe-CoS2@NC. The mass ratio of Fe2O3@CNHs / ZIF-67 powder to S powder was 1:3.

[0045] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a Fe-doped ZIF-67 derivative catalyst, characterized in that: The following steps are involved: Under argon, Fe2O3@CNHs / ZIF-67 powder and S powder were kept at 500-550℃ for 20-30 minutes to obtain Fe-doped ZIF-67 derivative catalyst.

2. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 1, characterized in that: The mass ratio of Fe2O3@CNHs / ZIF-67 powder and S powder is 1:3-1:

5.

3. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 1, characterized in that: Fe2O3@CNHs / ZIF-67 powder was prepared by the following process: 1) Add Co(NO3)2·6H2O or CoCl2·6H2O to a solution containing Fe2O3@CNHs powder, dimethylformamide and polyvinylpyrrolidone and stir to form a deposited Co 2+ Fe2O3@CNHs; 2) Deposition of Co 2+ 2-Methylimidazole, Co(NO3)2·6H2O and dimethylformamide were added to Fe2O3@CNHs and reacted by solvothermal method to obtain a nanocomposite catalyst.

4. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 3, characterized in that: In step 1), the dosage ratio of Fe2O3@CNHs powder, dimethylformamide, polyvinyl pyrrolidone and Co(NO3)2·6H2O or the dosage ratio of Fe2O3@CNHs powder, dimethylformamide, polyvinyl pyrrolidone and CoCl2·6H2O is 30-35 mg: 30-35 ml: 0.30-0.40 g: 2.91 -3.00 g.

5. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 3, characterized in that: In step 2), the usage ratio of 2-methylimidazole, Co(NO3)2·6H2O and dimethylformamide is 0.66-0.70 g: 0.58-0.60 g: 40-50 ml, and the usage ratio of 2-methylimidazole, CoCl2·6H2O and dimethylformamide is 0.66-0.70 g: 0.58-0.60 g: 40-50 ml.

6. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 3, characterized in that: The reaction temperature is 130-140°C and the reaction time is 24-26 hours.

7. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 3, characterized in that: Fe2O3@CNHs powders were prepared by positive pressure arc discharge method.

8. The method for preparing the Fe-doped ZIF-67 derivative catalyst according to claim 7, characterized in that: Fe2O3@CNHs powder is prepared by the following process: graphite rods are used as cathodes and anodes, Fe wire is inserted into the anode graphite rod, and discharge is carried out under a mixed gas of nitrogen and argon. The voltage between the cathode and the anode is 30 V, and the discharge current is 100-150 A to obtain the product. The product is heated at 400-550℃ for 30-60min to obtain Fe2O3@CNHs powder.

9. An Fe-doped ZIF-67 derivative catalyst prepared according to the method of claims 1-8.

10. Use of the preparation method of the Fe-doped ZIF-67 derivative catalyst prepared according to the method of claims 1-8 in electrocatalytic oxygen evolution reaction.